La condición de persona como fundamento del derecho en la iusfilosofía de Javier Hervada (2010)
This article pretends in a synthetic and valorative way —and from a mainly philosophicaljuridical perspective— to expound the human condition status as basis of the juridical reality within Javier Hervada ’s philosophy of law proposal. For this purpose we will first highlight the novelty of his juridical approach from an anthropological key, and then focus on its metaphysical conceptualization of the human person and its dignity from an examination of its fundamental ontological features. Then we will consider his iusnaturalistic realist proposal, demonstrating that it is the consequence of its essential anthropological foundations in the juridical field. In the light of these findings, we will discuss the issue of his immediate Law basis (anthropological) and the further one (theological) and finally, as a conclusion, offer a critical assessment of the researched matters.